The Combination of a Previous Kitchen Waste Grease Trap for Fat, Oil, and Grease for Pre-Treatment - Ali, Muhammad Akram Hakimi; Abu Talib, Siti Hidayah; Syed Hashim, Syarifah Intan Najla (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Fat, oil, and grease (FOG) contamination of wastewater is a significant problem for municipalities and operators of solid waste facilities. Restaurants and households are the higher contributions to the FOG entering the sewage system. Its discharge into the sewage system leads to a constant build-up that eventually causes sewer pipes to get clogged. Numerous scholars have examined FOG deposition concerning sewage conditions and local lifestyles. in addition, innovative technologies have been launched to the market that removes FOG from wastewater before its discharge into drainage and sewage systems. Grease interceptors, for example, are installed under certain restaurant kitchen sinks to collect grease from kitchen effluent. This technology is expensive, requires a lot of upkeep and space, and is often disregarded, resulting in odour discomfort. This research aims to modify a grease trap as the primary treatment method for untreated kitchen wastewater based on the gravity separation principle and to investigate the efficiency of grease trap physical treatment in a water treatment system used to filter oil and grease in the sink channel. Furthermore, when the outflow from the kitchen sink enters the grease trap, solid food particles sink into the grease trap while grease and oil float to the surface. The grease-free water goes into the septic system. Food particles in the waste food trap and floating oil and grease must be frequently removed. The optimization of the separation process was determined using a grease trap based on the flow rate of kitchen wastewater. The results revealed that the optimization removal of FOG was 99.54% with a 2.41 L/min of flow rate. Hence, this study shows the effectiveness of using grease traps could treat raw kitchen wastewater based on the gravity separation principle.